ANALISIS KETIADAAN NIAT (MENS REA) DALAM PEMIDANAAN PADA PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 844/PID.B/2019/PN.JKT.PST. - Edo Bintang Joshua; Ade Adhari (Jurnal Hukum Adigama, 2021)
In criminal law, punishment requires at least two conditions: subjective and objective conditions. To sentencing someone in the criminal court, it is not enough just by looking at their actions. Because criminal act are just one part of a condition in terms of punishments that are also called actus reus or physical elements. Mens rea is an essential part of criminal law. As one of terms of punishment, mens rea have a role as a subjective criminal in penal law. The absence of mens rea in any crime case makes the subjective criminal of the case missing. Sentencing someone who did a crime act without qualifying the mens rea element will injure the justice and set aside the mens rea as a subjective crimination. The case that was decided by Putusan Nomor 844/Pid.B/2019/PN.Jkt.Pst decided 29 (twenty nine) Sarinah mall employees. The decision clearly stated that the reasons for the perpetrators to commit the crime were based on a sense of humanity. This sense of humanity contradicts mens rea which is evil intent.